Preparation and thermal decomposition of copper(II), zinc(II) and cadmium(II) chelates with 8-hydroxyquinoline - Crespi, M. S.; Ribeiro, C. A.; Greenhalf, VCM; Zorel, H. E. (Soc Brasileira Quimica, 1999)
Through TG-DTA, DSC, elemental analysis, IR spectroscopy and X-ray, was verified that copper(II), zinc(II) and cadmium(II) 8-hydroxyquinolinate chelates prepared in acid medium present uncoordinated ligand into the crystal lattice. When the compounds are heated in an inert atmosphere it can he verified the consecutive partial sublimation, fusion, partial volatilization and partial thermal decomposition of the anhydrous complexes, When in an oxidating atmosphere the above process is only verified to Cu(II) chelates, Anhydrous copper(II) complexes present a monoclinic structure in the beta form and the volatilized compound in a alpha form. Zinc(II) and cadmium(II) hydrated complexes are isomorphous and they present different cell dimensions from those reported previously.
Keywords: 8-hydroxyquinolinates; TG; DTA